The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c8nj05842c
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered zeolitic imidazolate framework based self-templated synthesis of nitrogen-doped hollow porous carbon dodecahedrons as robust substrates for supercapacitors

Abstract: N-Doped hierarchical hollow porous carbon dodecahedrons derived from multi-layered core–shell ZIFs exhibit superior performance as supercapacitor electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Interestingly, a different experimental result was reported by Zhang et al. [ 156 ] Three‐layered ZIF‐67@ZIF‐8@ZIF‐67 and five‐layered ZIF‐67@ZIF‐8@ZIF‐67@ZIF‐8@ZIF‐67 composites can generate yolk–shell hollow Co@NC and yolk–double‐shell hollow Co@NC, respectively.…”
Section: Hollowing Mechanisms For Zif‐8/67 Derived Hcasmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, a different experimental result was reported by Zhang et al. [ 156 ] Three‐layered ZIF‐67@ZIF‐8@ZIF‐67 and five‐layered ZIF‐67@ZIF‐8@ZIF‐67@ZIF‐8@ZIF‐67 composites can generate yolk–shell hollow Co@NC and yolk–double‐shell hollow Co@NC, respectively.…”
Section: Hollowing Mechanisms For Zif‐8/67 Derived Hcasmentioning
confidence: 85%
“…For instance, a number of porous GO/ZIF composites have been successfully prepared in the manner of layered structures. [ 156–160 ] In addition, benefitting from its high flexibility, GO nanosheets can perfectly wrap ZIF nanocrystals to form a core–shell‐like ZIF@GO composite. Yamauchi's group reported a 2D heterostructural carbon nanosheets assembled 3D porous carbon framework (PCF), which is obtained by confined pyrolysis of GO‐wrapped ZIF‐8 composites (ZIF‐8@GO) ( Figure a).…”
Section: Hollowing Mechanisms For Zif‐8/67 Derived Hcasmentioning
confidence: 99%
“…Zeolitic imidazolate frameworks (ZIFs), with the advantages of regulable morphology, composition and functional diversity, have been utilized as an ideal template for synthesizing nanostructures. 20–22 Diversity of ZIFs and its derivatives with fine nanostructure such as NiCo 2− x Fe x O 4 nano boxes, 23 Co 9 S 8 nanoparticles, 24 double-shell ZnCoS dodecahedrons, 25 were synthesized and utilized in the fields of electrochemical catalysis, battery and supercapacitor. Tang et al reported mesoporous carbon composite with core–shell structure derived from dual-ZIF (ZIF8@ZIF-67), displaying superior capacitance of 270 F g −1 (1 A g −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[28] The carbonized ZIFs can produce porous activated carbon-containing pore regimes such as mesopores and micropores similar to activated carbons utilized in industry. [29,30] The material can also be used to synthesize advanced morphologies such as single-shell, double-shell, yolk-shell, yolk-double-shell, [31] and nanoleaves. [32] The material can also be used for the synthesis of heteroatom-doped carbon nanomaterials such as N/P co-doped carbon nanocages (NPCNs), [33] and N/P/S tri-doped hollow carbon nanocapsules (NPS-HCN).…”
Section: Introductionmentioning
confidence: 99%